2018
DOI: 10.1002/pola.29051
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain branched random polyethylene via acyclic diene metathesis (ADMET) copolymerization

Abstract: Five types of ethylene/α‐alkene model copolymers containing 21‐carbon alkyl branches have been synthesized via acyclic diene metathesis (ADMET) copolymerization. The overall branch content is controlled by varying the feedstock ratio of the long‐chain branched symmetrical α, ω‐diene and 1,9‐decadiene. Well‐defined melting transitions are present at low branch incorporation, followed by the broadening of the endotherms as the branch contents increase. However, instead of making the material amorphous, further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The ρ of LCB copolymer shown in Table is less than that of UL copolymer shown in Table , indicating that the molecular topological structure of the LCB copolymer is closer to solid spheres . The branching densities for LCB copolymers can be controlled by varying the feedstock ratios of the 1,7-octadiene or by controlling MA conversions …”
Section: Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The ρ of LCB copolymer shown in Table is less than that of UL copolymer shown in Table , indicating that the molecular topological structure of the LCB copolymer is closer to solid spheres . The branching densities for LCB copolymers can be controlled by varying the feedstock ratios of the 1,7-octadiene or by controlling MA conversions …”
Section: Results and Discussionmentioning
confidence: 97%
“…41 The branching densities for LCB copolymers can be controlled by varying the feedstock ratios of the 1,7-octadiene or by controlling MA conversions. 32 In Figure 5, the intrinsic viscosity ([η], from TD-GPC) of LCB copolymer (M n = 80200, PDI = 3.37) is lower than that UL copolymer (M n = 70200, PDI = 2.96) at a certain M w , indicating a constringent conformation of LCB copolymer. 42 And the slope of the Mark−Houwink−Sakurada curve for the LCB copolymer is less than that for UL copolymer, because the dendritic topology for LCB copolymer is more inclined to form solid sphere conformation.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…[13][14][15] Advanced polymer chemistry endows the accurate placement of the branching points along the backbone; namely, one could precisely adjust the spacing between the two adjacent side-chains, and thus, the grafting density. [16][17][18][19][20][21][22][23][24][25] Enlarged side-chain spacing would enable the recovery of at least part of the backbone flexibility of SCLCPs, thereby affording more possibilities of hierarchical self-organization. 18,19,23,[26][27][28][29][30] It has been demonstrated that, in addition to the coil conformation, when side-chain spacing is large enough, the backbones could even fold to form crystalline packing.…”
Section: Introductionmentioning
confidence: 99%